Fish environmental RNA enables precise ecological surveys with high positive predictivity - Kaede Miyata; Yasuaki Inoue; Yuto Amano; Tohru Nishioka; Masayuki Yamane; Takamitsu Kawaguchi; Osamu Morita; Hiroshi Honda (Ecological Indicators, 2021)
Metabarcoding analysis using environmental DNA (eDNA) is increasingly being used for monitoring biota. However, knowledge regarding abundance of fish environmental RNA (eRNA) and its utility in ecological survey is limited. In this study, we aimed to perform eDNA/eRNA metabarcoding analyses of fishes using water samples from rivers in Japan. Sufficient amounts of eRNA from various species were present in the environmental water samples, which can support ecological survey based on eRNA metabarcoding. The sensitivity of eRNA was equivalent to that of eDNA; however, its positive predictivity was superior to that of eDNA. In addition, correlation with abundance in the ecological survey was higher for eRNA than for eDNA. Only eRNA (and the ratio of eRNA and eDNA) enabled distinguishing saltwater or brackish water fishes (false positives) that could be generated due to contamination from domestic wastewater containing their corpses or body parts or from bird feces. To the best of our knowledge, this is the first report of the possibility of eRNA to serve as a critical indicator of living biotic assemblages that actually inhabit sampling points.